Frequency-integral method for impact damage detection in carbon fibre reinforced thermoplastic composites by Lamb waves - Šedek, Jakub; Šedková, Lenka; Vích, Ondřej (Ultrasonics, 2025)
The work deals with the detection and localization of impact damage in a carbon fibre reinforced thermoplastic composite using Lamb wave type of ultrasonic guided waves. The attention is paid to the universality and robustness of the evaluation process with emphasis on a frequency-integral method. The approach is presented on the composite plate subjected to the sequence of two impacts caused damage. The damage indication utilizes relative time-of-flight delays and the subsequent localization task introduces a novel correlation coefficient for damage indices used in RAPID visualisation algorithm. Generally, the selection of a suitable mode and actuating frequency is essential for the evaluation. On the contrary, it is shown that integral evaluation over wider frequency range works well and can eliminate inappropriate frequencies and other difficulties. The approach provides an overall view of the response of the measured composite plate in conjunction with the inspection system. The capability of the frequency-integral method is shown to be unlike the conventional evaluation process, which involves a chain of steps from Lamb wave tuning, identification of a particular wave packet, to damage determination. The method was implemented into LaWaI GUI (Lamb Waves Inspection Graphical User Interface) to automate the processing.
Keywords: Time-of-flight; Composite; Impact damage; Correlation coefficient; Multi-frequency approach; Frequency-integral method; Lamb waves